Defense Public Policy Regarding Human Resources Development in the context of Military Affairs Revolution - Lukman Yudho Prakoso (Syntax Literate, 2022)
The Man behind the gun, the defense of the country is a very important field to be realized to be strong, but many obstacles to achieving the desired defense goals, from various obstacles that are a priority is to provide quality human resources. In the midst of such a large globalization and as a democracy, public policy in the field of government on the management of civilian and military human resources is equally important in realizing human resources that can produce defense technologies that have a deterrence effect. Changes in defense technology are also related to the revolution in military affairs (RMA) which continues to move forward and affect the interaction of international relations. Taking into account the dynamics of international politics, RMA and human resources that exist today, the conceptual framework used in this paper cannot be separated from these aspects by sticking to the history and ideology of the Pancasila state. This is intended to realize reliable human resources without losing their identity to achieve Indonesia's national interests. In the face of change, the role of education is needed as an institution that continues to keep up with changes in actual and factual. In addition, research and development are also carried out by educational institutions in realizing reliable human resources. Similarly, in terms of defense, Indonesia already has an Indonesian Defense University related to defense topics. Cooperation with other educational institutions will automatically be carried out through each individual who has, is and will conduct research related to defense. The role of the Indonesian Defense University will be increasingly important in the future by building cooperation with educational institutions, research institutions, and so on in the civilian and military environments.